Microstructural Evolution of Large Cast Haynes 282 at Elevated Temperature - Yujin Yang (Crystals, 2021)
Haynes 282 has attracted attention for casting applications in AUSC power plants due to its good creep properties. However, the market is primarily comprised of wrought Haynes 282, while the cast version is not commercially available. In this study, the microstructure of a large traditional sand cast Haynes 282 was studied from as-cast condition to long-term heat-treated condition by combining experimental data and thermodynamic calculations. The microstructure of a large cast Haynes 282 includes γ, γ’, two types of MX, M23C6 and µ phases. After standard post heat treatment, µ phases were dissolved and precipitated as M6C. The equilibrium state was achieved after 266 h aging at 788 °C, after which γ’ particles began coarsening. These kept to a spherical morphology; the smallest misfit was found with the γ matrix. Once post heat treatment was finished, MX exhibited little morphology and compositional change during the long-term isothermal aging. Grain boundary is covered by discrete M23C6 and M6C precipitates and this morphology keeps stable during isothermal aging. No presence of the needle µ phase have been found at grain boundaries after 10,000 h aging at 788 °C. All these microstructural features indicated that cast Haynes 282 could have a high thermal stability and good creep properties.